Skin lesion segmentation using two-phase cross-domain transfer learning framework. (April 2023) - Karri, Meghana; Annavarapu, Chandra Sekhara Rao; Acharya, U Rajendra
Highlights: We present a novel two-phase such as model-level and data-level transfer learning approach for skin lesion segmentation using dermoscopic images. Our approach acquires dermoscopic and natural image knowledge, improving network training and performance. We present nSknRSUNet, a robust skin lesion segmentation network that uses a large receptive field block and spatial edge attention feature fusion module to segment skin lesions precisely. Numerous research on two dermoscopic datasets reveals that our approach can accurately segment skin lesions and significantly outperforms current methods. Abstract: Background and Objective: Deep learning (DL) models have been used for medical imaging for a long time but they did not achieve their full potential in the past because of insufficient computing power and scarcity of training data. In recent years, we have seen substantial growth in DL networks because of improved technology and an abundance of data. However, previous studies indicate that even a well-trained DL algorithm may struggle to generalize data from multiple sources because of domain shifts. Additionally, ineffectiveness of basic data fusion methods, complexity of segmentation target and low interpretability of current DL models limit their use in clinical decisions. To meet these challenges, we present a new two-phase cross-domain transfer learning system for effective skin lesion segmentation from dermoscopic images. Methods: Our system is based on two significant technical inventions. We examine a two- phase cross-domain transfer learning approach, including model-level and data-level transfer learning, by fine-tuning the system on two datasets, MoleMap and ImageNet. We then present nSknRSUNet, a high-performing DL network, for skin lesion segmentation using broad receptive fields and spatial edge attention feature fusion. We examine the trained model's generalization capabilities on skin lesion segmentation to quantify these two inventions. We cross-examine the model using two skin lesion image datasets, MoleMap and HAM10000, obtained from varied clinical contexts. Results: At data-level transfer learning for the HAM10000 dataset, the proposed model obtained 94.63% of DSC and 99.12% accuracy. In cross-examination at data-level transfer learning for the Molemap dataset, the proposed model obtained 93.63% of DSC and 97.01% of accuracy. Conclusion: Numerous experiments reveal that our system produces excellent performance and improves upon state-of-the-art methods on both qualitative and quantitative measures.